Does change in microcalcifications with neoadjuvant treatment correlate with pathological tumour response?. Issue 5 (May 2016) - Golan, O.; Amitai, Y.; Menes, T.
Abstract : Aim: To determine whether change in microcalcification density and extent after neoadjuvant treatment (NAT) can predict tumour response. Materials and methods: This single-institution, retrospective study included all women with breast cancer who underwent NAT between 1 January 2008 and 31 December 2014, and fulfilled the following criteria: mammography before NAT with pathological microcalcifications, mammography performed after NAT, and tumour resection at Tel-Aviv Sourasky Medical Center. Correlation was made between mammography features and clinicopathological information. Results: Fifty-four patients met the inclusion criteria. Post-NAT, the number of calcifications remained stable in 30 (55.5%) patients, decreased in 23 (42.6%) patients, and increased in one (1.9%) patient. Patients with a decreased number of malignant calcifications post-NAT had higher rates of pathological complete response compared to patients with no change (59% versus 20%, p =0.009). Patients with triple negative and human epidermal growth factor receptor 2 (HER2) receptor subtypes had higher rates of decreased number of calcifications post-NAT (50% versus 35%) and pathological complete response (57% versus 11%, p =0.007) compared to patients with luminal receptor subtype. In addition, patients who received a combination of chemotherapy and biological treatment had more cases of decreased number of calcifications compared to patients who received chemotherapy alone (56% versus 39%). No significant correlation was observed between calcification change post-NAT and calcification morphology or distribution pattern. Conclusions: Patients with breast carcinoma and decreased number of pathological calcifications post-NAT had higher rates of pathological complete response compared to patients with no change in calcifications; however, a substantial number of patients with complete pathological response had no change in microcalcification distribution with treatment, questioning the need to completely excise all calcifications post-NAT. Highlights: The number of microcalcifications can decrease with neoadjuvant treatment. Patients with decreased microcalcifications had more complete pathological response. Residual microcalcifications are not synonymous with residual disease.